Training for teachers in classroom action research at Yayasan Pendidikan Al-Mutawally Kuningan - Mahbub Nuryadien; Septiani Resmalasari (Universitas Muhammadiyah Magelang, 2023)
Teachers have other obligations related to developing abilities and skills as professional teachers. Based on teacher competency standards, one of the professional competencies that needs to be possessed is writing scientific papers. However, there are still many teachers who do not understand writing classroom action research, causing them to lag behind in terms of writing scientific papers. The purpose of this community service is to increase teacher understanding, knowledge, abilities and skills in writing classroom action research. The method used is the service learning approach. The results obtained from this training were an increase in the participants' understanding, abilities and skills in writing classroom action research. Participants are able to write down and know problems in class, class action research theory, prepare classroom action research proposals, conduct research, compile research reports to publish scientific papers.